2006
DOI: 10.1074/jbc.m607913200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into the Design of Nonpeptidic Isothiazolidinone-containing Inhibitors of Protein-tyrosine Phosphatase 1B

Abstract: Structural analyses of the protein-tyrosine phosphatase 1B (PTP1B) active site and inhibitor complexes have aided in optimization of a peptide inhibitor containing the novel (S)-isothiazolidinone (IZD) phosphonate mimetic. Potency and permeability were simultaneously improved by replacing the polar peptidic backbone of the inhibitor with nonpeptidic moieties. The C-terminal primary amide was replaced with a benzimidazole ring, which hydrogen bonds to the carboxylate of Asp 48 , and the N terminus of the peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 28 publications
2
57
0
1
Order By: Relevance
“…PTP1B gene knockout or antisense studies in normal and diabetic mice have shown lowered blood glucose levels and improved insulin responsiveness through enhanced IR signaling in peripheral tissues (Elchebly et al 1999;Klaman et al 2000;Zinker et al 2002). Therefore, PTP1B inhibitors have been pursued to develop novel anti-diabetic drugs (Xie and Seto 2007;Na et al 2006;Alal et al 2006;Shrestha et al 2007;Sparks et al 2007;Maccari et al 2007;Winter et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…PTP1B gene knockout or antisense studies in normal and diabetic mice have shown lowered blood glucose levels and improved insulin responsiveness through enhanced IR signaling in peripheral tissues (Elchebly et al 1999;Klaman et al 2000;Zinker et al 2002). Therefore, PTP1B inhibitors have been pursued to develop novel anti-diabetic drugs (Xie and Seto 2007;Na et al 2006;Alal et al 2006;Shrestha et al 2007;Sparks et al 2007;Maccari et al 2007;Winter et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, PTP1B inhibitors are potential therapeutic candidates to restore insulin sensitivity and treat T2DM. A series of PTP1B inhibitors containing highly charged, nonhydrolyzable phosphonate mimetic have been reported such as, difluoromethylene phosphonate, 2-carbomethoxybenzoic acid, and 2-oxalylaminobenzic acids (Ala et al, 2006;Johnson et al, 2002 due to poor cell membrane permeability, low oral bioavailability, and the difficulty in balancing the IR tyrosine kinase that is involved in downstream insulin signal phosphatases, such as PTP1B, that are required to shut down these signals. Therefore, small molecular and lipophilic PTP1B inhibitors with selectivity, bioavailability and acceptable pharmacokinetic properties have emerged as novel PTP1B drugs (Combs, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Due to lack of binding determinants, the C site to be less suitable than the A and B sites for structure-based design techniques, which often require accurate predictions of bound conformations of substituents. 18 The D site is a small narrow pocket, partially shielded from solvent and lined with polar and charged residues (Lys120, Lys116, Asp181, and Ser216, Fig. 1).…”
Section: Critical Residues Related To Selectivity In Ptp1bmentioning
confidence: 99%
“…1). 18 As this disordered site is positioned fairly close to the active site of PTP1B, it is possible to increase potency and elicit selectivity with only a small increase in molecular weight. 19 …”
Section: Critical Residues Related To Selectivity In Ptp1bmentioning
confidence: 99%